Long-term outcomes in syncope patients presenting to the emergency department: A systematic review. Issue 1 (January 2020) - Leafloor, Cameron W.; Hong, Patrick Jiho; Mukarram, Muhammad; Sikora, Lindsey; Elliott, Jesse; Thiruganasambandamoorthy, Venkatesh
ABSTRACT: Introduction: Long-term outcomes among syncope patients are not well studied to guide physicians regarding outpatient testing and follow-up. The objective of this study was to conduct a systematic review for outcomes at 1-year or later among ED syncope patients. Methods: We searched Cochrane Central, Medline, Medline in Process, PubMed, Embase, and the Cumulative Index to Nursing databases from inception to December 2018. We included studies that reported long-term outcomes among ED syncope patients. We excluded studies on patients <16 years old, studies that included syncope mimickers (pre-syncope, seizure, intoxication, loss of consciousness after head trauma), case reports, letters to the editor, non-English and review articles. Outcomes included death, syncope recurrence requiring hospitalization, arrhythmias and procedural interventions for arrhythmias. Meta-analysis was performed by pooling the outcomes using random effects model. Results: Initial literature search generated 2, 094 articles duplicate removal. Of the 50 articles selected for full-text review, 19 articles with 98, 211 patients were included in this review: of which 12 were included in the 1-year outcome meta-analysis. Pooled analysis showed : 7.0% mortality; 16.0% syncope recurrence requiring hospitalization; 6.0% with device insertion. 1-year arrhythmias reported in two studies were 1.1 and 26.4%. Pooled analysis for outcome at 31 to 365 days showed: 5.0% mortality and 1% device insertion. Two studies reported 4.9% and 21% mortality at 30 months and 4.2 years follow-up. Conclusions: An important proportion of ED syncope patients suffer long-term morbidity and mortality. Appropriate follow-up is needed and future research to identify patients at risk is needed.